Intramolecular Electric Field Construction in Metal Phthalocyanine as Dopant‐Free Hole Transporting Material for Stable Perovskite Solar Cells with >21 % Efficiency. Issue 12 (12th February 2021) - Yu, Zefeng; Wang, Luyao; Mu, Xijiao; Chen, Chun‐Chao; Wu, Yiying; Cao, Jing; Tang, Yu
Abstract: Low conductivity and hole mobility in the pristine metal phthalocyanines greatly limit their application in perovskite solar cells (PSCs) as the hole‐transporting materials (HTMs). Here, we prepare a Ni phthalocyanine (NiPc) decorated by four methoxyethoxy units as HTMs. In NiPc, the two oxygen atoms in peripheral substituent have a modified effect on the dipole direction, while the central Ni atom contributes more electron to phthalocyanine ring, thus efficiently increasing the intramolecular dipole. Calculation analyses reveal the extracted holes within NiPc are mainly concentrated on the phthalocyanine core induced by the intramolecular electric field, and further to be transferred by π‐π stacking space channel between NiPc molecules. Finally, the best efficiency of PSCs with NiPc as dopant‐free HTMs realizes a record value of 21.23 % (certified 21.03 %). The PSCs also exhibit the good moisture, heating and light stabilities. This work provides a novel way to improve the performance of PSCs with free‐doped metal phthalocyanines as HTMs. Abstract : A Ni phthalocyanine (NiPc) decorated by four methoxyethoxy units with a strong intramolecular electric field is prepared and used as hole‐transporting materials (HTMs) in perovskite solar cells (PSCs). The best PSCs with NiPc as dopant‐free HTM show a record efficiency of 21.23 % (certified 21.03 %). The PSCs also exhibit the excellent stability.